Developing the intervention material to increase physical activity levels of European preschool children: the ToyBox‐study. (August 2014) - Duvinage, K.; Ibrügger, S.; Kreichauf, S.; Wildgruber, A.; De Craemer, M.; De Decker, E.; Androutsos, O.; Lateva, M.; Iotova, V.; Socha, P.; Zych, K.; Mouratidou, T.; et al.
Summary: Early childhood is an important period for adopting positive health‐related behaviours. More than 95% of European preschool children attend kindergartens, making these settings ideal for the implementation of health promotion interventions. The ToyBox‐intervention addressed preschool children, their parents/caregivers and teachers. The aim of the intervention was to improve four energy balance‐related behaviours (i.e. healthy snacking, water consumption, physical activity and sedentary behaviour) by implementing a kindergarten‐based, family‐involved intervention in six European countries (Belgium, Bulgaria, Germany, Greece, Poland and Spain). The intervention material was developed following the intervention mapping protocol, taking into account local and cultural differences among the intervention countries. The present paper focuses on the development of the physical activity component of the intervention. Parental involvement was addressed by providing parents/caregivers with two newsletters, two tip cards and a poster. Teachers received a handbook with guidance on environmental changes in the classroom, 26 physical education sessions and suggestions for fun, interactive classroom activities aiming at total class participation to increase preschoolers' physical activity levels. The ToyBox‐intervention material was distributed according to a standard time frame. Teachers received their material prior to the start of the intervention and parents/caregivers received their material during the intervention when each energy balance‐related behaviour was implemented.